Synthesis, Characterization, and Photoelectrochemical Catalytic Studies of a Water‐Stable Zinc‐Based Metal–Organic Framework. Issue 3 (15th January 2018) - Altaf, Muhammad; Sohail, Manzar; Mansha, Muhammad; Iqbal, Naseer; Sher, Muhammad; Fazal, Atif; Ullah, Nisar; Isab, Anvarhusein A.
Abstract: Metal–organic frameworks (MOFs) are class of porous materials that can be assembled in a modular manner by using different metal ions and organic linkers. Owing to their tunable structural properties, these materials are found to be useful for gas storage and separation technologies, as well as for catalytic applications. A cost‐effective zinc‐based MOF ([Zn(bpcda)(bdc)] n ) is prepared by using N, N ′‐bis(pyridin‐4‐ylmethylene)cyclohexane‐1, 4‐diamine [ N, N ′‐bis(pyridin‐4‐ylmethylene)cyclohexane‐1, 4‐diamine] and benzenedicarboxylic acid (bdc) linkers. This new material exhibits remarkable photoelectrochemical (PEC) catalytic activity in water splitting for the evolution of oxygen. Notably, this non‐noble metal‐based MOF, without requiring immobilization on other supports or containing metal particles, produced a highest photocurrent density of 31 μA cm −2 at 0.9 V, with appreciable stability and negligible photocorrosion. Advantageously for the oxygen evolution process, no external reagents or sacrificial agents are required in the aqueous electrolyte solution. Abstract : Zinc or swim : A zinc‐based metal– organic framework (MOF) exhibits remarkable photoelectrochemical (PEC) catalytic activity in water splitting for the evolution of oxygen. This non‐noble metal‐based MOF, without requiring immobilization on other supports or containing metal particles, produces a highest photocurrent density of 31 μA cm −2 at 0.9 V with appreciable stability and negligible photocorrosion.